Mazhab dan Pemikiran Ekonomi Islam Kontemporer - Ishandawi; Yadi Janwari; Dedah Jubaedah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The increasingly complex dynamics of the global economy require the presence of an economic system that is comprehensive and in harmony with universal values. In this context, Islamic economics appears as an alternative paradigm by offering a concept based on sharia principles. To answer the challenges of the modern era, various schools of thought and contemporary Islamic economic thought have emerged which seek to integrate Islamic values ​​with the latest developments in economic science. This article aims to explore these schools of thought and thought, as well as analyze their contribution and influence in the development of Islamic economics in the contemporary era. By using literature studies, this study explains the main principles, figures, as well as the advantages and limitations of the Iqtishaduna school of thought, Nejatullah Siddiqi's thoughts, Mannan's economic concepts, and other contemporary thinkers. Apart from that, this article also reviews the practical developments of contemporary Islamic economics, such as the birth of sharia financial institutions, the role of study centers, as well as the dynamics of scientific publications and discussions related to this topic. The results of the discussion show that contemporary Islamic economic schools and thought have made a significant contribution to enriching the Islamic economic scientific body and offering an alternative economic system that is just. However, comprehensive implementation of this concept still faces various challenges that require continuous efforts from various parties. In the future, the development of contemporary Islamic economics needs to continue to be carried out by reviewing previous thinking and formulating new approaches according to the dynamics of the times to create an economic order that is rahmatan lil 'alamin.